Variable speed wind turbine with external stiffness and rotor deviation observer - Kamarudin, Muhammad Nizam (Trans Tech Publications, 2014)
Often in prominent literature, the appearance of external stiffness in wind turbine dynamical model has been neglected. The ignorance of external stiffness eliminates the presence of rotor-side angular deviation in the system dynamic. In order to give more practical look of the variable speed control system structure, we develop a linear observer to estimate the rotor angular deviation. We use Linear Quadratic Regulator (LQR) to design the observer gain, as well as the estimation error gain. To facilitate observer design, the system is linearized around its origin by using Jacobian matrix. By using the estimated rotor angular deviation, we design a variable speed control via Lyapunov and Arstein to enhance power output from the turbine.